HDL-C is inversely associated with the incidence of osteoarthritis among the USA: evidence from the NHANES program of 1999–2020 - Man Fang; Jing Lei; Wei Hu; Junxiao Yang; Ting Lei; Yitian Lei; Long Hua (Scientific Reports)
Abstract Osteoarthritis (OA) has been the most common arthritis affecting public health all over the world. Previous experimental research reported that increased low-density lipoprotein cholesterol, along with decreased high-density lipoprotein cholesterol may be associated with increased ectopic bone formation and possible knee OA, while clinical evidence is absent. This study aimed to investigate the association between blood high-density lipoprotein cholesterol (HDL-C) and OA. In this cross-sectional study, all the data were acquired from the National Health and Nutrition Examination Survey (NHANES) program from 1999 to 2020. The blood lipid metabolites of each participant were acquired from the laboratory data, using the standard approach. The diagnosis of OA was established through a questionnaire interview. The multivariate logistic regression analysis, subgroup analysis, and smooth curve fitting analysis were applied to investigate the association between the blood lipid metabolites and OA after adjusting with covariates including gender, age, race, BMI, marital status, physical activity, smoking, hypertension, and diabetes. The interaction analysis and Subgroup analysis were also performed. A total of 28,933 participants, including 3710 people with self-reported OA and 25,223 people without arthritis, were finally eligible for inclusion in this study. The multiple logistic regression indicated that in the 3rd and 4th quartiles, the HDL-C level showed a positive association with the risk of OA (Q3: OR = 1.1342, 95% CI 1.0071, 1.2773, p < 0.05; Q4: OR = 1.2354, 95% CI 1.0937, 1.3956, p < 0.001). The smooth curve fitting showed a trend that the OA odds ratio increased with the increase of HDL-C. Subgroup analysis continued to show that increased HDL led to increased OA risk at certain quartiles in different subgroups. This study shows a positive correlation between blood HDL-C levels and osteoarthritis (OA) risk, suggesting HDL-C may be a risk factor. Further research is needed, especially on lipid-lowering drugs like statins, which can affect HDL-C and influence this association.